2014
DOI: 10.1007/s40489-014-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Social Skill Group Interventions for Adolescents with Autism Spectrum Disorders: a Systematic Review

Abstract: This article reviews the available literature on group-based social skills interventions for adolescents with autism. Forty-four studies were identified that were published in peer-reviewed journals. While each identified treatment utilized a group format, there was significant heterogeneity among the implemented procedures and evaluative methods. Studies were compared on a number of dimensions, and trends in the field were identified. The findings suggest that there is significant evidence for the usefulness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 57 publications
(122 reference statements)
0
39
0
1
Order By: Relevance
“…Rao et al 2008;Reichow et al 2012;Miller et al 2014). These reviews have shown how SST groups may improve the social skills of some children and adolescents with ASD, but highlight the need for further research measuring broader outcomes, such as quality of life.…”
Section: Review Objectivesmentioning
confidence: 99%
“…Rao et al 2008;Reichow et al 2012;Miller et al 2014). These reviews have shown how SST groups may improve the social skills of some children and adolescents with ASD, but highlight the need for further research measuring broader outcomes, such as quality of life.…”
Section: Review Objectivesmentioning
confidence: 99%
“…However, despite their widespread use, very little rigorous, well-designed research has been conducted to examine their efficacy (Kasari, Shire, Factor, & McCracken, 2014). Indeed, while there have been more than a dozen systematic reviews of GSSIs conducted in recent years (e.g., Barry et al, 2003; Blacher, Kraemer, & Schalow, 2003; Elder, Caterino, Chao, Shacknai, & De Simone, 2006; Flynn & Healy, 2012; Kaat & Lecavalier, 2014; Kasari & Patterson, 2012; Koenig, De Los Reyes, Cicchetti, Scahill, & Klin, 2009; McMahon, Lerner et al, 2013; Miller, Vernon, Wu, & Russo, 2014; Otero, Schatz, Merrill, & Bellini, 2015; Rao, Beidel, & Murray, 2008; Reichow & Volkmar, 2010; Schreiber, 2011; Spence, 2003; White, Keonig, & Scahill, 2007), there has only been one meta-analysis to evaluate efficacy of GSSIs (Reichow, Steiner, & Volkmar, 2012). This sole meta-analysis – which focused on well-designed randomized controlled trials (RCTs) with a wait-list control, of which only five were evident at the time – provided initial support for the efficacy of GSSIs for improving social competence for ASD youth.…”
Section: Introductionmentioning
confidence: 99%
“…To date, reviews of social skills group literature for individuals with ASD have evaluated research focusing on children and adolescents (Miller, Vernon, Wu, & Russo, ; Rao, Beidel, & Murray, ; Reichow et al., ), adolescents and adults (Hotton & Coles, ) or only adults with ASD without intellectual disability (Spain & Blainey, ). These reviews concluded that social skills groups for individuals with ASD were effective for reducing a number of social difficulties.…”
Section: Introductionmentioning
confidence: 99%